Amerikan ve Türk hukukunda taşıyanın yüke özen yükümlülüğünün ihlalinden dolayı sorumluluğu - Akan, Pınar (My University, 2001)
Türk Ticaret Kanunu(TTK),taşıyanın esas itibariyle iki ayrı sorumluluk halini düzenlemiş olup bunlardan birincisi;taşıyanın yolculuğun başlangıcında geminin denize,yola ve yüke elverişsizliği nedeniyle(gecikme dahil)meydana gelen tüm zararlardan sorumluluğu(TTK m.1019), diğeri ise;tez konumuz olan taşıyanın yüke özen gösterme yükümlülüğünün ihlali sonucu yükte meydana gelen ziya ya da hasardan sorumluluğudur.(TTK m:1061-vd.) Türk Hukukunda TTK m.1061 ve devamı maddeler incelenmiş olup, Amerikan Hukukunda ise bu hususta taşıyanın sorumluluğunu düzenleyen 1893 tarihli Harter Yasası(ki söz konusu yasa ABD limanları arasında yapılan taşımalardan doğan uyuşmazlıklara uygulanmaktadır) ve 1936 tarihli COGSA(Carriage of Goods by Sea Act)ki bu yasa da ABD limanları ile yabancı ülke limanları arasında yapılan arasında yapılan taşımalardan doğan uyuşmazlıklara uygulanmaktadır, incelenmiştir. Tez konumuz olan sorumluluğun şartları kısaca şunlardır: 1-Taşıyanın yüke özen gösterme yükümlülüğünün ihlali Taşıyan,yükün yüklenmesi,istifi,taşınması,elden geçirilmesi ve boşaltılmasında tedbirli bir taşıyanın dikkat ve ihtimamını göstermekle yükümlüdür.Söz konusu yükümlülük hem TTK m.1061'de,hem de COGSA m.3(2)de yer almakta olup özel ve ayrıcalıklı bir yükümlülüktür,başkasına devredilemez. 2-Yüke özen yükümlülüğünün ihlalinde taşıyan ya da adamlarının kusuru bulunmalıdır. Burada taşıyanın adamları kavramından gemi adamları,kendi adamları ve yardımcı şahıslar anlaşılmaktadır. Kusur ise ikiye ayrılmaktadır: a-Teknik kusur(sevk ve idare kusuru) b-Ticari kusur(yükün menfaati icabı alınması gereken önlemlerin alınmamış olması) Bazı durumlarda hangi kusur tipinin mevcut bulunduğunu ayırdetmekte güçlük doğmaktadır.Bu hususta kıstas;menfaat icabı alınması gereken önlemlerin yükü mü yoksa gemiyi mi ilgilendirdiğidir. 3-Yük zıyaa ya da hasara uğramalıdır. 4-Zarar,yükün taşınmak üzere teslim alındığı andan teslim edildiği ana kadar geçen süre içinde zıya ya da hasarı yüzünden meydana gelmiş olmalıdır. Zıya ya da hasarın ihbar süresi bu durumun haricen belli olması durumunda derhal, haricen belli olmaması halinde ise teslimden itibaren 3 gündür.Bu sürelere uyulmaması halinde ispat külfeti yer değiştirir. Malların tesliminden ya da teslimi gereken tarihten itibaren 1 yıl içinde taşıyan aleyhine mahkemeye müracaat edilebilir. Bu süre hak düşürücü bir süredir. Taşıyanın sorumluğu nedeniyle ödeyeceği tazminatın kapsamı da yükün varma limanında ve teslim edilmesi gereken tarihteki piyasa değeridir. Yük değerinin yükleme başlamadan önce bildirilmemiş ve bu beyanın konişmentoya yazılmamaış olması halinde beher koli ya da parça başına TTK uyarınca 100000 TL;COGSA uyraınca ise 500 USD esası uygulanacaktır.

Under Turkish and American Maritime Law,the carrier has basicly two duties: a-The duty of the carrier to make the vessel seaworthy and to provide a proper ship; b-The duty to properly load,handle and care for cargo. In case of the breach of the duties,mentioned above,the carrier is liable. In Turkish Maritime Law,Turkish Commercial Code(TTK)Art. 1061and continuing articles;in American Maritime Law dealing articles in the Harter Act(which applies to all contracts for carriage of goods by sea between the ports of the United States)and Art 3&4 of COGSA(Carriage of Goods by Sea Act;which applies to all contracts of carriage of goods by sea to or from ports of the United States in foreign trade)are studied in this thesis. The conditions of the liability of the carrier in the case of breach of the duty of care are: 1--There must be a breach of duty of care. The carrier shall properly and carefully load,handle,stow,carry,keep,care for and discharge the goods carried. This duty is both mentioned in Art. 1061 of TTK in Turkish Maritime Law and Art. 3(2)of COGSA in American Maritime Law. The duty of care of the cargo is non-delegable. 2-There must be negligence of the crew and other agents of the carrier. The carrier is accordingly responsible for the acts of the master,the crew and his other agents. Negligence can be divided in two groups: a-Neglect in the navigation or management of the ship b-Neglect in duty of care of cargo When the defense is neglect in the navigation or management of the ship,however it is sometimes difficult to distinguish this type of fault- for which the carrier is not responsible-from negligence in loading,stowage,custody,care or discharge of the cargo-for which the carrier is responsible.The test to differentiate these two categories of fault is whether the negligent act or omission relates primarily to the vessel as such or whether it relates specifically to the cargo. 3-Cargo must be damaged. 4-Cargo must be damaged during the voyage. During the voyage means, the entire period during which the goods are in the carrier's charge at the port of loading and discharged at the port of discharge. Unless notice of loss or damage must be given in writing to the carrier or his agent at the port of discharge before or at the time of the removal of the goods into the custody of the person entitled to delivery under the contracts of carriage,such removal will be prima facie evidence of the delivery by the carrier of the goods as described in the bill of lading. If loss or damage is not apparent,the notice must be given within three days of the delivery. Failure to give notice within the three day notice period does not affect or prejudice the right of the shipper to bring suit;it affects the burden of proof. The carrier will also be discharged from all liability in respect of loss or damage unless the suit is brought within one year after delivery of the goods or the date when the goods should have been delivered. The measure of the shipper's recovery when cargo is damaged is normally the difference between the fair market value of the goods at the port of destination in the condition they were in when shipped and their value as damaged. The carrier-in any event-will not be responsible in an amount exceeding 100000 TL(according to TTK)or 500 USD( according to COGSA)per package or in case of the goods not shipped in packages,per customary freight unit,unless the nature and value of such goods have been declared by the shipper before shipment and inserted in the bill of lading.
Keywords: Hukuk; ÖZEL HUKUK; Taşımacılık